You need to recognize the formula `sin(a+b) = sin a*cos b + sin b*cos a` . You need to put `a = 60^o` and `b = 15^o` , such that:
`sin(60^o + 15^o) = sin 60^o *cos 15^o + sin 15^o*cos 60^o `
`sin 75^o = sin 60^o *cos 15^o + sin 15^o*cos 60^o `
Hence, the given expression could be evaluated as the sine of the sum of angles `60^o ` and `15^o` ,...
You need to recognize the formula `sin(a+b) = sin a*cos b + sin b*cos a` . You need to put `a = 60^o` and `b = 15^o` , such that:
`sin(60^o + 15^o) = sin 60^o *cos 15^o + sin 15^o*cos 60^o `
`sin 75^o = sin 60^o *cos 15^o + sin 15^o*cos 60^o `
Hence, the given expression could be evaluated as the sine of the sum of angles `60^o ` and `15^o` , such that `sin 60^o *cos 15^o + sin 15^o*cos 60^o = sin 75^o .`
No comments:
Post a Comment